Burundi: International Pressure and Counter-Sanctional Maneuvering of Ruling Elites - FITUNI Leonid Leonidovich (Ученые записки Института Африки Российской академии наук)
Using the example of one of the poorest and economically most vulnerable states in the world – the Republic of Burundi – the article examines the impact of international sanctions on foreign and domestic policy as well as upon the economic situation in sovereign states of African. The author demonstrates that, despite the severe destructive consequences of the economic and political sanctions of external players, the use of restrictive regimes against “recalcitrant” actors of interstate relations does not automatically lead to a change in their line of behaviour or to the downfall of the ruling regimes. As the example of Burundi shows, even in the conditions of the poorest country in the world, well-thought-out political maneuvering and reasonable use of available resources can allow the targeted state and its elites to remain in power indefinitely and to maintain the political status quo.